Liver stiffness measurement and spleen diameter as predictors for the presence of esophageal varices in chronic hepatitis C patients. Issue 46 (November 2017) - Tag-Adeen, Mohammed; Alsenbesy, Mohamed; Ghweil, Ali Abdelrahman; Abd Elrazek, M. Ali Hussein; Elgohary, Elsayed A.; Sallam, Mohammad M.; Ismael, Ali; Nawara, Abdallah
Abstract : Abstract: Although it is an invasive and unpleasant procedure, esophagogastroduodenoscopy (EGD) is still the gold standard for esophageal varices (EV) detection. The aim of this study was to investigate liver stiffness measurement (LSM) and spleen diameter as simple noninvasive tools for EV prediction in chronic hepatitis C patients (CHC). A total of 123 Egyptian patients with CHC have been included and were classified based on screening EGD result into 2 groups; group A (without EV) and group B (with EV). Group (B) was subclassified according to EV grade into 4 subgroups: (B1, grade I), (B2, grade II), (B3, grade III), and (B4, grade IV). LSM was taken for each patient on the next day by an independent Fibroscan operator and correlated to the EGD result. Demographic, clinical, and biochemical data were recorded and analyzed using advanced data-mining computational technology. Mean LSM was 9.94 ± 6 kPa for group A and 33.32 ± 14 kPa for group B, whereas it was 21.22 ± 3, 25.72 ± 6, 33.82 ± 8, and 46.1 ± 15 kPa for subgroups B1, B2, B3, and B4, respectively. Mean spleen diameter was 11.09 ± 1.7 cm for group A and 16.58 ± 1.6 cm for group B. However, LSM ≥17 kPa was the only independent factor for EV prediction; splenic longitudinal span ≥15 cm was a complementary predictor when LSM was <17 kPa. The overall accuracy was 98.33 ± 3.33, Mikro = 98.26%. LSM ≥17 kPa and spleen diameter ≥15 cm is a simple noninvasive algorithm that could be used for prediction of EV and discrimination among its different grades.